Quorum Sensing Regulates the Hydrolytic Enzyme Production and Community Composition of Heterotrophic Bacteria in Coastal Waters - Urvoy, Marion; Lami, Raphaël; Dreanno, Catherine; Delmas, Daniel; L’Helguen, Stéphane; Labry, Claire (Frontiers in Microbiology, 2021)
Heterotrophic microbial communities play a central role in biogeochemical cycles in the ocean by degrading organic matter through the synthesis of extracellular hydrolytic enzymes. Their hydrolysis rates result from the community’s genomic potential and the differential expression of this genomic potential. Cell-cell communication pathways such as quorum sensing (QS) could impact both aspects and, consequently, structure marine ecosystem functioning. However, the role of QS communications in complex natural assemblages remains largely unknown. In this study, we investigated whether N-acylhomoserine lactones (AHLs), a type of QS signal, could regulate both hydrolytic activities and the bacterial community composition (BCC) of marine planktonic assemblages. To this extent, we carried out two microcosm experiments, adding five different AHLs to bacterial communities sampled in coastal waters (during early and peak bloom) and monitoring their impact on enzymatic activities and diversity over 48 h. Several specific enzymatic activities were impacted during both experiments, as early as 6 h after the AHL amendments. The BCC was also significantly impacted by the treatments after 48 h, and correlated with the expression of the hydrolytic activities, suggesting that changes in hydrolytic intensities may drive changes in BCC. Overall, our results suggest that QS communication could participate in structuring both the function and diversity of marine bacterial communities.